Awareness of Self Examination for Breast Cancer among Women of Karachi (Medical Forum Monthly, 2024)
Objective: To assess the awareness of self-examination and symptoms of breast leading to breast cancer in women above 40 year of ages. And to assess the awareness of risk factors and screening test leading to breast cancer in women above 40 year of ages.Study Design: Descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at the OPDs of Jinnah Post Graduate Medical Center at Karachi from November 2017 to February 2018.Materials and Methods: The sample size of 284 women above 40 years of age was drawn through non-probability purposive sampling technique at surgical OPDs of Jinnah Post Graduate Medical Center at Karachi. A structured questionnaire regarding awareness about self-examination, risk factors, symptoms and screening test of breast diseases was constructed. Data was collected through the structured questionnaire. Pilot study was done to check the authenticity of questionnaire. Data was entered and analyzed on statistical package for social sciences (SPSS version 20) with 95% confidence interval and 5% margin of error. P-value less than 0.05 was considered statistically significant.Results: The results showed insufficient knowledge regarding breast diseases in women above 40 years of age. 65 % (0.001) of the women did not know how to self-examine themselves. 64.4% (0.003) agreed breast lump was common in married women. 65.8% (0.059) considered Breast feeding as a cause of Breast lump. 70.1 % (0.000) of them were unaware of the screening test. 53.2% (0.002) didn’t take redness of breast seriously. 53.2% (0.055) didn’t consider irritation or inward folding of the nipple as a symptom of breast cancer. 65.2% didn’t know about risk factors such as contraceptives which can lead to breast cancer. 46% women of age’s b/w 40-45 were eager to had knowledge about breast self-examination and risk factors.Conclusion: Study concluded the women’s lack of awareness about self-examination, symptoms and screening test of breast lump which can easily be cancerous due to lack of knowledge. The study will divert the attention of health concerned authorities towards this growing threat by promoting awareness among women and providing proper facilities for the screening programs and early diagnosis.